2016
DOI: 10.2196/mhealth.5855
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Mind Wandering, Affect, and Sleep: An Ecological Momentary Assessment

Abstract: BackgroundA considerable portion of daily thought is spent in mind wandering. This behavior has been related to positive (eg, future planning, problem solving) and negative (eg, unhappiness, impaired cognitive performance) outcomes.ObjectiveBased on previous research suggesting future-oriented (ie, prospective) mind wandering may support autobiographical planning and self-regulation, this study examined associations between hourly mind wandering and moderate-to-vigorous physical activity (MVPA), and the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
1
18
1
Order By: Relevance
“…Ehlers et al [48] demonstrated success in a 14-day pilot study with a low-cost approach that used participants’ mobile phones, text messaging, and mobile Internet to explore daily relationships between self-worth and physical activity in middle-aged women. Fanning et al [49] used a similar approach in a 7-day study of college-aged adults examining mind wandering.…”
Section: Discussionmentioning
confidence: 99%
“…Ehlers et al [48] demonstrated success in a 14-day pilot study with a low-cost approach that used participants’ mobile phones, text messaging, and mobile Internet to explore daily relationships between self-worth and physical activity in middle-aged women. Fanning et al [49] used a similar approach in a 7-day study of college-aged adults examining mind wandering.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that it is difficult to generalize our findings because of small sample size and nonprobability sampling methods. However, prior usability studies have suggested that a small number of participants, as few as 5 to 20, with similar background show great potential for exploring a variety of perspectives that can identify a vast amount of design problems [ 54 , 55 ]. In addition, because of scheduling and transportation constraints of breastfeeding women, it is almost impossible to recruit probability samples.…”
Section: Discussionmentioning
confidence: 99%
“…Another 2 EMA studies were conducted in a different population (college students), with 1 work focused on mind wandering [ 33 ] and the other on general time use (vs specific behavior/s), like this study [ 34 ]. These examinations differed from the prior 2 EMA studies as assessments were conducted via an app on mobile phones/PDAs designed to capture activities in the past hour or 20 min, respectively (involved less retrospection).…”
Section: Discussionmentioning
confidence: 99%
“…These examinations differed from the prior 2 EMA studies as assessments were conducted via an app on mobile phones/PDAs designed to capture activities in the past hour or 20 min, respectively (involved less retrospection). Comparisons with this study include similar or longer follow-up periods (hourly assessments for 1 week and twice daily assessments for 3 weeks, respectively) and the use of text messages [ 33 ] or push notifications with alarms [ 34 ] to prompt participant responses. Our study required participant initiation of the app to track time use.…”
Section: Discussionmentioning
confidence: 99%